1998
DOI: 10.5694/j.1326-5377.1998.tb140159.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of systematic reviews of randomised trials by Australian neonatologists and obstetricians

Abstract: Objective: To determine what proportion of Australian neonatologists and obstetricians report using systematic reviews of randomised trials. Design: Cross‐sectional survey using structured telephone interviews. Setting: Australian clinical practice in 1995. Participants: 103 of the 104 neonatologists in Australia (defined as clinicians holding a position in a neonatal intensive care unit); a random sample of 145 members of the Royal Australian College of Obstetricians and Gynaecologists currently practising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Seventy‐five full‐text articles were excluded because they did not address perceived facilitators, systematic reviews, meta‐analyses or the databases associated with them. Fifteen unique studies reported in 15 articles 2,4,10,12,15 –25 met inclusion criteria. Figure 1 outlines the search process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy‐five full‐text articles were excluded because they did not address perceived facilitators, systematic reviews, meta‐analyses or the databases associated with them. Fifteen unique studies reported in 15 articles 2,4,10,12,15 –25 met inclusion criteria. Figure 1 outlines the search process.…”
Section: Resultsmentioning
confidence: 99%
“…The communication of clinically important research findings is hampered by the volume and geometric growth of the medical literature. Systematic reviews can address this problem 2 . A systematic review is a review of a clearly formulated question that uses systematic and explicit methods to identify, select and critically appraise relevant research and to collect and analyse data from studies that are included in the review 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These results differ from an Australian information retrieval service in which, of 18 service users who responded, four felt it was ‘likely’ and 11 indicated that it was ‘very likely’ that they would alter clinical practice as a result of the information provided 9 . A study of Australian neonatologists and obstetricians found that 72% of neonatologists reported reading systematic reviews and that 58% of this group changed their practice in response to the systematic review 10 …”
Section: Discussionmentioning
confidence: 99%
“…With their history of networking, New Zealand NICUs were also eager to join, and in 1995, all 22 NICUs in Australia and all 6 in New Zealand (Table 1) were collecting the minimum data set. A few ( n : 6) NICUs took time to adapt their local data collection to include all ANZNN items, 7 but this was soon rectified. Table 1 lists the participating members of the ANZNN showing the later inclusion of all New Zealand level II nurseries and increasing participation of those in Australia.…”
Section: The Australian and New Zealand Neonatal Network (Anznn)mentioning
confidence: 99%